Evaluasi User Experience pada Game Grand Theft Auto (GTA) V Online menggunakan Cognitive Walkthrough - Muhammad Hasbi Rahman; Eriq Muhammad Adams Jonemaro; Wibisono Sukmo Wardhono (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
User experience is the study of how to create a product that is comfortable and easily understood by the product user. One concrete way to find out whether the user experience is functioning properly or not is by using the Cognitive Walkthrough method. This method is analytic to evaluate step-by-step in a product and find out the problem of user convinience of the product. This method is suitable for both new and old users because it does not require a lot of money, it is effective, and efficient. Game Grand Theft Auto V online is a game that is very suitable to be the object of Cognitive Walkthrough evaluation research because it has received many awards, some of them are winning the Game Of The Year at Spike VGX and the Golden Joystick Award in 2013 and winning Best Multiplayer at Spike VGX in 2014. The game evaluation results show that there is a problem of task importance 1 with a feedback problem type with an average value of 0.666, while in task importance 2 a user problem type (U) with an average value of 1.5, physical demand (P) with an average value of 0.55 and hidden (H) with an average value of 0.166, and the last problem lies in task importance 4 with the types of user (U), hidden (H) and physical demand (P) problems with an average value of 0.166 each.